2019
DOI: 10.4314/jasem.v23i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Characterization of Abandoned Dumpsite Soil Properties for Pre- Foundation Delineation at Bowen University Campus, Iwo, Nigeria

Abstract: Geophysical investigation and microstudy of soil properties were carried out within Bowen University, for the characterization of the subsurface pattern in the area using vertical electrical sounding (VES) survey and evaluation of soil properties with a view to mapping subsurface geological features, such as weak and competent zones and to determine the overburden thickness of the area for pre-foundation studies for a proposed high-rise building. Four (4) VES was carried out in the study area employing schlumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This will reveal whether the subsurface acts as protective potentials against the contaminant that could percolate down to the available groundwater. It has been shown from different research that the geophysical method of subsurface investigation is accurate and reliable when measuring the parameter that is associated with the subsurface structures in groundwater potential and dumpsite assessment as reported in literature [8][9][10]. Telford et al [11] reported that geophysical investigation of the subsurface offers moderately rapid, fast, and costeffective ways to derive enormous area informatio n analysis of subsurface geology.…”
mentioning
confidence: 99%
“…This will reveal whether the subsurface acts as protective potentials against the contaminant that could percolate down to the available groundwater. It has been shown from different research that the geophysical method of subsurface investigation is accurate and reliable when measuring the parameter that is associated with the subsurface structures in groundwater potential and dumpsite assessment as reported in literature [8][9][10]. Telford et al [11] reported that geophysical investigation of the subsurface offers moderately rapid, fast, and costeffective ways to derive enormous area informatio n analysis of subsurface geology.…”
mentioning
confidence: 99%